Synthesis and characterization of various type of Azines as potential bioactive agents - How, Fiona Ni Foong; Abdul Malek, Nurfathiah; Solachuddin Jauhari, Arief Ichwan (2013)
Five Azines (HMB, ANGDA, HHS, HBrS and EMB) were successfully synthesized and evaluated for their antimicrobial activities against various strains of microbes and cytotoxic activities against human breast adenocarcinoma (MCF-7) and non-small lung carcinoma (H1299) cell lines. All the compounds were characterized with FTIR spectroscopy and further confirmed with single crystal X-Ray diffraction analyses. Screening of antimicrobial activities showed HMB was selectively against K. pneumonia and C. albicans. Cytotoxic activity was evaluated against breast adenocarcinoma, MCF-7 and non-small lung, H1299 cancer cell lines. All of the compounds were active, particularly ANGDA and HMB were tested to be most potent against both MCF-7 and H1299 cell lines.